2009
DOI: 10.1371/journal.pone.0006727
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic CHD1L Expression in Mouse Induces Spontaneous Tumors

Abstract: BackgroundAmplification of 1q21 is the most frequent genetic alteration in hepatocellular carcinoma (HCC), which was detected in 58–78% of primary HCC cases by comparative genomic hybridization (CGH). Using chromosome microdissection/hybrid selection approach we recently isolated a candidate oncogene CHD1L from 1q21 region. Our previous study has demonstrated that CHD1L had strong oncogenic ability, which could be effectively suppressed by siRNA against CHD1L. The molecular mechanism of CHD1L in tumorigenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…We have demonstrated that 1) CHD1L-transfected cells are able to form more colonies in soft agar and caused tumor formation in nude mice; 2) the transformation ability of CHD1L is effectively inhibited by small interference RNA (siRNA) against CHD1L; 3) CHD1L can promote the G 1 /S transition and inhibit apoptosis in response to cellular stress [33] . Importantly, there is now a transgenic mouse model with ubiquitous CHD1L expression [55] . Spontaneous tumor formation was found in 10/41 (24.4%) of CHD1L-transgenic mice including 4 mice with HCCs, and no cases were seen in their 39 wild-type littermates [55] .…”
Section: Shc1mentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that 1) CHD1L-transfected cells are able to form more colonies in soft agar and caused tumor formation in nude mice; 2) the transformation ability of CHD1L is effectively inhibited by small interference RNA (siRNA) against CHD1L; 3) CHD1L can promote the G 1 /S transition and inhibit apoptosis in response to cellular stress [33] . Importantly, there is now a transgenic mouse model with ubiquitous CHD1L expression [55] . Spontaneous tumor formation was found in 10/41 (24.4%) of CHD1L-transgenic mice including 4 mice with HCCs, and no cases were seen in their 39 wild-type littermates [55] .…”
Section: Shc1mentioning
confidence: 99%
“…Importantly, there is now a transgenic mouse model with ubiquitous CHD1L expression [55] . Spontaneous tumor formation was found in 10/41 (24.4%) of CHD1L-transgenic mice including 4 mice with HCCs, and no cases were seen in their 39 wild-type littermates [55] . Further, our mechanistic studies of CHD1L in the past two years have delineated CHD1L-involved hepatocarcinogenesis during HCC progression and metastasis.…”
Section: Shc1mentioning
confidence: 99%
“…ALC1 was originally identified as a gene present on a short human chromosome 1q21 region that is amplified in hepatocellular carcinomas (1). Overexpression of the ALC1 protein was found to transform human cells and to be oncogenic in mice (1,2). More recently, the ALC1 gene was found to be mutated in patients with congenital anomalies of the kidney and urinary tract (3).…”
mentioning
confidence: 99%
“…More recently, the ALC1 gene was found to be mutated in patients with congenital anomalies of the kidney and urinary tract (3). Although the mechanism of ALC1 action in these processes is not known, ALC1 has been reported to have roles in DNA repair (4) and in controlling the expression of several genes implicated in tumorigenesis and metastasis (1,2,5).…”
mentioning
confidence: 99%
“…The percentage of cells in the S phase was significantly reduced in the si-CHD1L-treated cells compared with the control-si-treated cells. It was reported that in a transgenic mouse model, CHD1L could facilitate DNA synthesis and G1/S transition through the up-regulation of Cyclins (A, D1, and E), CDK2, 4, and down-regulation of Rb, p27 (Kip1), and p53 (Chen et al 2009b;Liu et al 2012). In our study, the CHD1L expression was decreased obviously and it was in accordance with the up-regulation of p53 and p21, down-regulation of cyclin E and Cdk2 (Fig.…”
Section: Knockdown Of the Expression Of Chd1l Inhibited The Proliferamentioning
confidence: 99%